Efeito farmacogenético e farmacogenômico do metotrexato na citotoxicidade de células mononucleares periféricas do sangue - Barbisan, Fernanda (2014)
Methotrexate (MTX) is an antimetabolite drug analogue of folic acid with wide clinical application, used in high doses for the treatment of cancer and in low doses for the treatment of autoimmune diseases such as rheumatoid arthritis and psoriasis. Although effective, the MTX has several side effects. The oxidative stress seems to be involved with the toxicity caused by the MTX in various organs. Despite the effect on the imbalance of oxidative metabolism, the influence of polymorphisms of antioxidant enzymes on MTX toxicity is not well studied. In this context, the present study aimed to examine whether the Ala16Val polymorphism of the antioxidant enzyme superoxide dismutase manganese dependent (SOD2), which affects the efficiency of the detox enzyme, could have an effect on the cytotoxic response to MTX. For this, an in vitro study using peripheral blood mononuclear cells (PBMC) obtained from healthy donors harboring different genotypes of polymorphism Ala16Val-SOD (= genotypes AA, VV and AV) was performed. Once obtained, PBMCs were treated with MTX at concentrations of 10 and 100 μM for 24 and 72 hours and analyzed for the effect on viability, modulation of the oxidative metabolism-inflammatory and apoptotic. PBMC-AA which have a naturally SOD2 30 to 40% more efficient than the PBMC- VV, showed more resistance to treatment with MTX compared to PBMC-AV/VV assessed. As production levels of EROS and lipid peroxidation significantly increased in cells exposed to MTX, regardless of genotype, however, increased levels of protein carbonylation were observed only in PBMC-AV/VV. The PBMC-AA demonstrated decreased activity of SOD2 and the levels of glutathione peroxidase with PBMC-AA were higher. The levels of caspase-8 and -3 were increased in PBMC exposed to MTX, but the modulation of these genes, as well as Bax and Bcl-2 genes involved in apoptotic route, was genotype dependent. The MTX was able to raise the levels of inflammatory cytokines and decrease the level of anti-inflammatory cytokine IL-10, regardless of genotype. The results suggest that Ala16Val-SOD2 polymorphism is capable of modulating the cytotoxic response of PBMC to the MTX.